Thermal Weakening Friction During Seismic Slip: Experiments and Models With Heat Sources and Sinks. Issue 5 (18th May 2021) - Nielsen, S.; Spagnuolo, E.; Violay, M.; Di Toro, G.
Abstract: Experiments that systematically explore rock friction under crustal earthquake conditions reveal that faults undergo abrupt dynamic weakening. Processes related to heating and weakening of fault surfaces have been invoked to explain pronounced velocity weakening. Both contact asperity temperature T a and background temperature T of the slip zone evolve significantly during high‐velocity slip due to heat sources (frictional work), heat sinks (e.g., latent heat of decomposition processes), and diffusion. Using carefully calibrated High‐Velocity Rotary Friction experiments, we test the compatibility of thermal weakening models: (1) a model of friction based only on T in an extremely simplified, Arrhenius‐like thermal dependence; (2) a flash heating model which accounts for the evolution of both V and T ; (3) same but including heat sinks in the thermal balance; and (4) same but including the thermal dependence of diffusivity and heat capacity. All models reflect the experimental results but model (1) results in unrealistically low temperatures and model (2) reproduces the restrengthening phase only by modifying the parameters for each experimental condition. The presence of dissipative heat sinks in stage (3) significantly affects T and reflects on the friction, allowing a better joint fit of the initial weakening and final strength recovery across a range of experiments. Temperature is significantly altered by thermal dependence of (4). However, similar results can be obtained by (3) and (4) by adjusting the energy sinks. To compute temperature in this type of problem, we compare the efficiency of three different numerical approximations (finite difference, wavenumber summation, and discrete integral). Plain Language Summary: During earthquakes, fast slip on the fault generates large amounts of localized heat. The consequent temperature rise has been proposed as one main cause of abrupt frictional weakening, concomitant with decomposition reactions, which act as heat sinks, partially buffering the temperature rise. Here we test models of thermal weakening by computing the temperature evolution and the temperature‐dependent friction, showing the importance of accounting for heat sources, heat sinks, and local variation of rock properties due to rising temperatures. Key Points: Thermal dependence of diffusivity and heat capacity can have a large effect on temperature and friction during co‐seismic slip The effects of thermal dependence on friction can be approximately emulated in a model with constant parameters by tuning the energy sinks We compare the efficiency of three different numerical solutions (Finite differences, wavenumber summation, and integral solution